Profil Indeks Larva pada Delapan Wilayah Puskesmas di Surabaya - LYNDA ROSSYANTI; DWI SUSANTI; IVAN RAHMATULLAH; DWI PENI KARTIKASARI; SUKMAWATI BASUKI; HENY ARWATI; INDAH TANTULAR; SUHINTAM PUSARAWATI; HERU PRASETYO; SRI HIDAJATI; SUBAGYO YOTOPRANOTO; SRI WIJAYANTI SULISTYAWATI (HANG TUAH MEDICAL JOURNAL, 2020)
ABSTRACT Background : Dengue virus infection is still a health problem in Surabaya. On 2015 Insidence Rate (IR) for Surabaya is 22.50 and the Case Fatality Rate (CFR) is 2%. This figure has decreased compared to 2014, but has not met the target achievement indicator for the P2DBD target CFR <1%. Method : The study was conducted in the rainy season, May 2015 in several Puskesmas areas in Surabaya. Samples were randomly selected as many as 378 houses spread in eight health centers (Pegirian, Krembangan Selatan, Hamlet Wall, Tambak Rejo, Putat Jaya, Simomulyo, Sawahan and Tanahkali Kedinding). The larvae survey was conducted using the single larva method. Larvae were taken from breeding sites and stored in specimen bottles for species identification at the Parasitology Laboratory Faculty of Medicine Universitas Airlangga. Result : The highest House Index (HI) was obtained (60.46%) or the 39.54% larvae free rate in Simomulyo and the lowest HI (33.33%) or 66.67% ABJ in Pegirian Puskesmas. Larvae species identification showed 100% was Aedes aegypti. The high HI value at the Simomulyo Health Center is not in line with the number of cases of dengue virus infection in 2015 which was 4 cases. Whereas in Pegirian Health Center with the lowest HI value found 11 cases. Discussion : These results could be due to the possibility because the study did not calculate larval density and high population mobility in the area.